THE RELATIONSHIP BETWEEN FACIAL SHAPE AND TOOTH SHAPE AGES 12-14 YEARS OLD IN SOUTH DAHA - Rahmad Arifin; Muhammad Aminullah Majedi; Fitriana Caessar Pertiwi; Sherly N Sinay (FKG Unlam, 2022)
Introduction: The facial and maxillary central incisor shape is classified into triangular, oval, and square. There is a correlation between the facial shape and maxillary permanent central incisors. This theory is still used to determine tooth selection and determine aesthetics when restoring incisors. This study aims to determine the relationship between facial shape and tooth shape aged 12-14 years in Daha Selatan. Methods: The research was conducted using observational analytics with a cross-sectional approach and using a non-parametric test Spearman Rho correlation. Results: 76 people (89.4%) had an ovoid facial shape with an ovoid tooth, 3 people had an ovoid facial shape with a square tooth shape, and 3 people had an ovoid facial shape with tapering teeth form as many as 6 people (7.1%). While the sample that has a square facial shape with a square tooth shape is 14 people (87.5%), 2 people have a square facial shape with an ovoid tooth shape (12.5%), and a square facial shape with a tapering tooth shape is 0 (0 %). As for the sample that has a tapering facial shape with a tapering tooth shape for as many as 4 people (80%), a tapering facial shape with an ovoid tooth shape for as much as 1 person (20%) and there are no samples with a tapering facial shape with a square tooth shape. Conclusion: There is a relationship between the facial shape and The tooth shape aged 12-14 years in Daha Selatan (90.57%). Keywords : Facial Shape, South Daha, Tooth Shape